Vitamin B12 Deficiency among Boarding School Children from Seven Districts of Bhutan - Dzed, Laigden; Pokhrel, Hari Prasad; Zangpo, Loday; Pelzom, Dorji; Dendup, Ugyen (International Journal of Innovative Research in Medical Science, 2019)
Introduction: Bhutanese school children are vulnerable to vitamin B12 deficiency as outbreaks of micronutrient deficiency diseases have been a common occurrence. The study presents the status of vitamin B12 deficiency among boarding school children from those seven districts. Methods: A cross-sectional study was conducted to determine serum vitamin B12 level. Data and blood samples were collected from 448 boarding school children from the seven districts of Bhutan. Serum cobalamin levels were assessed and relationship between factors analyzed. Results: The study found that 64 % of the school children were found to have vitamin B12 deficiency. Adjusted Odds Ratio for the vitamin deficiency among boarding school children from lower secondary and higher secondary schools were 4.05 and 3.3 respectively, when compared to those from the primary school. Starches were the most commonly served foods in boarding schools, while the animal source foods were served twice or less in a month. Conclusion: The study found a high prevalence of Vitamin B12 deficiency among boarding school children from seven districts. Boarding school meals had very less frequency of animal source foods.